Assessing the Effectiveness of Correctional Sanctions - Cochran, Joshua C. (Journal of quantitative criminology, 2014)
Objectives Despite the dramatic expansion of the US correctional system in recent decades, little is known about the relative effectiveness of commonly used sanctions on recidivism. The goal of this paper is to address this research gap, and systematically examine the relative impacts on recidivism of four main types of sanctions: probation, intensive probation, jail, and prison. Methods Data on convicted felons in Florida were analyzed and propensity score matching analyses were used to estimate relative effects of each sanction type on 3-year reconviction rates. Results Estimated effects suggest that less severe sanctions are more likely to reduce recidivism. Conclusions The findings raise questions about the effectiveness of tougher sanctioning policies for reducing future criminal behavior. Implications for future research, theory, and policy are also discussed.